2022
DOI: 10.3390/buildings12070890
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Perception in Naturally Ventilated University Buildings in Spain during the Cold Season

Abstract: The indoor thermal environment has become a critical factor, due to its impact on the energy efficiency of a building and the health and performance of its occupants. It is particularly important for educational buildings, where students and teachers are exposed to these thermal conditions. This study assessed the impact of natural ventilation efficiency and university students’ thermal perception during the cold season. A field monitoring campaign and a questionnaire survey were conducted. A total of 989 stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 32 publications
2
8
0
Order By: Relevance
“…It was also found that hotness feelings from male and female students differed significantly (p < 0.001). For female students, the neutral temperature was one degree higher than for male students 34 . The optimal indoor temperature for high performance of office duties is 25.8 °C, and when the temperature was 22.0-26.0 °C, workers' productivity did not significantly decline 35 36 37 .…”
Section: Introductionmentioning
confidence: 75%
“…It was also found that hotness feelings from male and female students differed significantly (p < 0.001). For female students, the neutral temperature was one degree higher than for male students 34 . The optimal indoor temperature for high performance of office duties is 25.8 °C, and when the temperature was 22.0-26.0 °C, workers' productivity did not significantly decline 35 36 37 .…”
Section: Introductionmentioning
confidence: 75%
“…Another relevant aspect is addressed in Ascione et al's research [101], which draws attention to the lack of consideration in many certifications regarding crucial aspects of the built environment, such as seismic risks, environmental threats, climate change, urban heat islands, and external light and noise pollution. This underscores the urgency of reviewing or establishing new standards, especially concerning ventilation, which has gained prominence due to the COVID-19 pandemic [102]. Lee and Park [103] emphasize that biophilic design has been the subject of increasing research due to the pandemic, climate change, and environmental concerns, aiming to enhance the quality of life in environments by providing users with better experiences and more positive emotions.…”
Section: Environmental Impact and Risk Assessment For Sustainable Bui...mentioning
confidence: 99%
“…In general, companies increasingly need to develop strategies that improve efficiency, satisfaction and health, aiming for sustainable returns in the long term [147]. In this sense, the literature has identified future trends, including integrating the IoT, sensors and High Dynamic Range (HDR) imaging techniques to monitor IEQ parameters [27,102,148] to increase the measurement accuracy. In addition, there is the development of real-time ventilation control algorithms [140], personalized ventilation innovations, sensing and management [104], and the computational analysis of air distribution in the environment employing Computational Fluid Dynamics (CFD) [149] to optimize the ventilation rate and air quality [150,151] and thus reduce the incidence of allergic and infectious diseases and Sick Building Syndrome (SBS), among others [82].…”
Section: Future Trends and Research Gapsmentioning
confidence: 99%
“…Monitoring the thermal environment of buildings is critical for assessing the performance of existing structures and identifying cost-effective energy-saving solutions (Zhang and Li, 2020;Aguilar et al, 2022). Therefore, a lot of research has been conducted on monitoring the thermal environment impact on outdoor and indoor scenarios (Han et al, 2022;Li et al, 2022).…”
Section: Introductionmentioning
confidence: 99%